The Impact of Short Video Platforms’ Destination Attractiveness Online Review and Influencer Credibility on Tourist Attitude on Travel Intention - Tsabita, Putri Raka; Alfansi, Lizar (Universitas Muhammadiyah Pontianak, 2025)
The increasing reliance on short video platforms like TikTok, YouTube Shorts, and Instagram Reels has shifted how individuals form travel intentions. Pinpointing how platform quality, influencer credibility, destination attractiveness, online reviews, and parasocial bonds turn this deluge into genuine travel intention is therefore essential. This study clarifies the pathways through which those five factors build attitudes toward destinations and convert them into intention to visit. Using purposive sampling, 300 Indonesian SVP users completed an online questionnaire; data were analysed with SEM-PLS to evaluate a seven-construct model. SVP quality—usefulness, ease of use, and enjoyment—emerged as the strongest driver of travel intention. Influencer credibility and destination attractiveness significantly bolstered positive attitudes. Parasocial interaction intensified the credibility-to-attitude link, while online reviews showed no direct effect on travel intention. Intention to travel peaks when informative, intuitive, and entertaining SVPs showcase appealing destinations through trusted influencers who feel personally familiar. This study introduces an integrated model combining technology-acceptance, social-learning, and parasocial lenses, and destination appeal to explain how short video content drives modern travel intention.